Persistent chlorinated organic contaminants in harbour porpoises from the North Sea, the Baltic Sea and Arctic waters - Bruhn, Regina; Kannan, Narayanan; Petrick, Gert; Schulz-Bull, Detlef E.; Duinker, Jan C. (Science of The Total Environment, 1999)
Individual chlorinated biphenyls (CBs) and chlorinated pesticides (p,p′-DDT and metabolites, HCHs and HCB) were determined in blubber samples of 40 harbour porpoises (Phocoena phocoena) of different age and sex from the North Sea, the Baltic Sea and Greenland coastal waters. Polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs) were analysed in a selected group of animals. ΣCB concentrations (medians) in North Sea immature specimens were similar (14.9 μg/g lipid) to those from the Baltic Sea (17.0 μg/g lipid) and exceeding those in Greenland specimens by an order of magnitude (1.3 μg/g lipid). The median concentrations (μg/g lipid) of HCB, p,p′-DDE, p,p′-DDD and γ-HCH were in the order Greenland<North Sea<Baltic Sea. The highest concentrations of α-HCH (0.14 μg/g lipid) were found in the Greenland population, and p,p′-DDT was detected only in this group. The North Sea and Baltic Sea populations were identified as distinctly separate on the basis of levels and compositions of these contaminants. The ecological risk associated with dioxin-like toxicity was dominated by the CB congeners 118 and 170; the PCDD/Fs were playing only a minor role.